The global spread of hepatitis C virus 1a and 1b: a phylodynamic and phylogeographic analysis - Magiorkinis, G; Magiorkinis, E; Paraskevis, D; Ho, S; Shapiro, B; Pybus, O; Allain, J; Hatzakis, A (Public Library of Science, 2009)
Background: Hepatitis C virus (HCV) is estimated to affect 130-180 million people worldwide. Although its origin is unknown, patterns of viral diversity suggest that HCV genotype 1 probably originated from West Africa. Previous attempts to estimate the spatiotemporal parameters of the virus, both globally and regionally, have suggested that epidemic HCV transmission began in 1900 and grew steadily until the late 1980s. However, epidemiological data suggest that the expansion of HCV may have occurred after the Second World War. The aim of our study was to elucidate the timescale and route of the global spread of HCV. Methods and findings: We show that the rarely sequenced HCV region (E2P7NS2) is more informative for molecular epidemiology studies than the more commonly used NS5B region. We applied phylodynamic methods to a substantial set of new E2P7NS2 and NS5B sequences, together with all available global HCV sequences with information in both of these genomic regions, in order to estimate the timescale and nature of the global expansion of the most prevalent HCV subtypes, 1a and 1b. We showed that transmission of subtypes 1a and 1b "exploded" between 1940 and 1980, with the spread of 1b preceding that of 1a by at least 16 y (95% confidence interval 15-17). Phylogeographic analysis of all available NS5B sequences suggests that HCV subtypes 1a and 1b disseminated from the developed world to the developing countries. Conclusions: The evolutionary rate of HCV appears faster than previously suggested. The global spread of HCV coincided with the widespread use of transfused blood and blood products and with the expansion of intravenous drug use but slowed prior to the wide implementation of anti-HCV screening. Differences in the transmission routes associated with subtypes 1a and 1b provide an explanation of the relatively earlier expansion of 1b. Our data show that the most plausible route of the HCV dispersal was from developed countries to the developing world.